2021
DOI: 10.21203/rs.3.rs-148356/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of Biomarkers for Amyotrophic Lateral Sclerosis and Frontotemporal Lobar Degeneration From Human Cerebrospinal Fluid Using Mass Spectrometry-Based Proteomics

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) are progressive neurodegenerative diseases that share clinical and neuropathologic features. Critical to the mission of developing effective therapies for ALS and FTLD is the discovery of biomarkers that can illuminate shared mechanisms of neurodegeneration, which can then be evaluated for diagnostic, prognostic or pharmacodynamic value across the disease spectrums. MethodsHere, we merged unbiased discovery-based approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 47 publications
5
11
1
Order By: Relevance
“…Using a simplified pre‐analytical preparation protocol combined with label‐free LC–MS/MS in DIA mode, we were able to quantify a total of 1832 protein groups from only 50 μL of CSF and identified alterations in the levels of individual CSF proteins and network‐level changes in people with ALS. This depth is similar to that achieved with DIA in recent studies for non‐fractionated CSF (1493–1732 proteins, Cho et al., 2021; Karayel et al., 2022), although somewhat lower than previous studies in ALS that have made use of labelling methods (1936–2303 proteins, Barschke et al., 2020; Oeckl et al., 2020; Oh et al., 2023). Importantly, however, the DIA approach resulted in a much lower rate of missing values than typically achieved with DDA, with between‐group comparisons carried out on 1593 proteins after a stringent (50% per group) filtering threshold, thus allowing for highly robust comparisons.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Using a simplified pre‐analytical preparation protocol combined with label‐free LC–MS/MS in DIA mode, we were able to quantify a total of 1832 protein groups from only 50 μL of CSF and identified alterations in the levels of individual CSF proteins and network‐level changes in people with ALS. This depth is similar to that achieved with DIA in recent studies for non‐fractionated CSF (1493–1732 proteins, Cho et al., 2021; Karayel et al., 2022), although somewhat lower than previous studies in ALS that have made use of labelling methods (1936–2303 proteins, Barschke et al., 2020; Oeckl et al., 2020; Oh et al., 2023). Importantly, however, the DIA approach resulted in a much lower rate of missing values than typically achieved with DDA, with between‐group comparisons carried out on 1593 proteins after a stringent (50% per group) filtering threshold, thus allowing for highly robust comparisons.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in the lysosomal storage disorder Gaucher disease, for which secreted CHIT1 is a key diagnostic marker (Hollak et al., 1994), the characteristically lipid‐laden macrophages show increases in the abundance of chemokine CCL18 and Glycoprotein nonmetastatic melanoma protein B (GPNMB) that are typically more indicative of alternatively activated microglia (Hüttenrauch et al., 2018; Kramer et al., 2016; Zigdon et al., 2015). Whilst significantly increased abundance was not found in this study, GPNMB has also been identified as increased in CSF of ALS patients in other studies (Oeckl et al., 2020; Oh et al., 2023). Given that in transgenic SOD1 models of ALS there is evidence for a shift from alternatively activated to classically activated microglia over the disease course (Gravel et al., 2016; Liao et al., 2012), defining the specific activation state of the cellular source of all the chitinase proteins in CSF will further contribute to understanding of the contribution of neuroinflammation to the clinical heterogeneity of the disease.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations